PENERAPAN MODEL PEMBELAJARAN STUDENT ACTIVE LEARNING UNTUK MENINGKATKAN KETERAMPILAN BERBICARA SISWA KELAS III MADRASAH IBTIDAIYAH AL-ABRAR KOTA MAKASSAR - putri nadhira azaliya; Andi Adam; Abd Rajab (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Speaking skills are one of the fundamental competencies that are important to develop from an early age. Therefore, a learning model that encourages students to be active in the learning process is needed. This study aims to improve and enhance students' speaking skills through the implementation of the Student Active Learning (SAL) model in Grade III of Madrasah Ibtidaiyah Al-Abrar. The type of research used is classroom action research, which consists of two cycles, with each cycle carried out in three meetings. The procedure of this research consists of four stages: planning, implementation, observation, and reflection. The subjects of this study were 28 third-grade students at MI Al-Abrar. The results of this study show that in the first cycle, only 11 students, or around 39%, achieved the Minimum Mastery Criteria (MMC). However, in the second cycle, all 28 students, or 100%, met the MMC, and the class average also reached 100%, which is categorized as high. Based on the results of this study, it can be concluded that the implementation of the Student Active Learning model can improve the speaking skills of third-grade students at MI Al-Abrar.